2012
DOI: 10.1093/ckj/sfs114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enzyme replacement therapy on serum asymmetric dimethylarginine levels, coronary flow reserve and left ventricular hypertrophy in patients with Fabry disease

Abstract: BackgroundFabry disease (FD) is a rare disorder and one of the causes of progressive renal and cardiac dysfunction. FD results from an X-linked recessive lysosomal storage disorder caused by a defect in the gene encoding lysosomal α-galactosidase A. Although accumulation of globotriaosylceramide leads to renal and cardiac manifestations, the precise mechanisms remain unclear. Coronary microvascular dysfunction may be one of the causes of cardiac complications in FD. We aimed to assess coronary flow reserve (CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Eight mixed-ERT OS publications (including some large, long-term studies including ≤100 patients followed for ≤120 months) agreed that ERT might slow the decrease in eGFR [51,103,104,107,109,112,114,116]. One large, long-term OS publication reported that patients without proteinuria responded better to treatment than patients with overt proteinuria (109 patients followed for ≤116 months) [103].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight mixed-ERT OS publications (including some large, long-term studies including ≤100 patients followed for ≤120 months) agreed that ERT might slow the decrease in eGFR [51,103,104,107,109,112,114,116]. One large, long-term OS publication reported that patients without proteinuria responded better to treatment than patients with overt proteinuria (109 patients followed for ≤116 months) [103].…”
Section: Resultsmentioning
confidence: 99%
“…Findings from mixed-ERT studies were reported across nine OS publications [101,104,107,109,110,112,113,114,116] including a large study in 100 patients followed for 59–64 months [114]. One OS publication showed that patients with an abnormal baseline electrocardiogram (ECG) had a statistically significant increase in LVMi, while patients with normal ECG at baseline did not experience any statistically significant change in LVMi (neither progression nor regression) with mixed-ERT treatment (6 years’ follow-up) [113].…”
Section: Resultsmentioning
confidence: 99%
“…Several our clinical studies assessed CFR using transthoracic Doppler echocardiography (Fig. 2) [20, 2224], a non-invasive and safe method that does not involve the risk of radiation exposure. Our data showed that CFR was significantly associated with the estimated glomerular filtration rate (eGFR) in hypertensive patients without a significant coronary artery stenosis (Fig.…”
Section: Endothelial Dysfunction Of Coronary Arterymentioning
confidence: 99%